Evaluation Of Medicinal Properties Of Chestnut Fruit Used In The Treatment Of Varicose Diseases By Chemical Composition - Madaminova Gulassal Abdurauf qizi; Xojiqulov Azizbek Sobirovich; Asqarov Ibrohim Rahmonovich (Genius Journals, 2023)
The article provides information on the importance of vitamins used in the treatment of varicose veins, and the determination of the amount of water-soluble vitamins in an aqueous extract of chestnut fruits using the "High-Performance Liquid Chromatography" method.
Keywords: anti-varicose drugs; treatment with vitamin C; vitamin B1